Regulatory Technology (Reg Tech) as an enhancement of compliance processes in financial institutions - Dziawgo, Tomasz (Copernican Journal of Finance & Accounting, 2025)
This paper explores the evolving role of Regulatory Technology (Reg Tech)as a transformative catalyst in financial compliance. Emerging after intensified regulatoryrequirements post-2007–2009 subprime financial crisis, Reg Tech leveragestechnologies such as artificial intelligence (AI), machine learning (ML), blockchain, orcloud computing to enhance both efficiency and effectiveness of compliance processesin financial institutions. Based on academic literature, industry reports, and realworldcase studies, the paper examines key advantages of Reg Tech adoption, includingreduced compliance costs, improved risk detection, and enhanced reporting accuracy. It also highlights main barriers such as legacy IT systems, data privacy concerns, andskill gaps within compliance teams. From a policy perspective, the paper analyzes howregulatory authorities are embracing Supervisory Technology (Sup Tech) to modernizeoversight functions, improve data collection, and strengthen market surveillance. Thedual perspective – Reg Tech for institutions and Sup Tech for regulators – underscoresthe broader digital transformation of financial regulation. The paper concludes withpolicy recommendations aimed at fostering Reg Tech adoption through regulatory clarity,innovation facilitators, skills development, and stakeholder collaboration. Overall,the study provides a holistic assessment of how technology is reshaping compliance inthe financial sector and identifies critical enablers for its responsible and scalable deployment. Among research questions are: What are the current advantages and risksof adopting Reg Tech solutions in financial institutions? What technological, organizational,and regulatory barriers hinder broader adoption? The hypothesis to be testedis as follows: Reg Tech adoption enhances regulatory compliance processes in financialinstitutions. In research paper, the following methods are leveraged: qualitativemethodological approach focusing primarily on systematic review of academic literatureand industry reports on the issue in question, comparative case study analysis ofReg Tech deployment within highlighted financial institutions as well as Sup Tech deploymentswithin selected regulatory institutions, secondary expert insights gatheredfrom white papers and publicly available data. Based on the above-mentioned methodologicalapproach, the hypothesis was tested positively.